2017
DOI: 10.1001/jamacardio.2016.4792
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Major Adverse Cardiovascular and Cerebrovascular Events Associated With Noncardiac Surgery

Abstract: Importance Major adverse cardiovascular and cerebrovascular events (MACCE) are a significant source of perioperative morbidity and mortality following non-cardiac surgery. Objective To evaluate national trends in perioperative cardiovascular outcomes and mortality after major non-cardiac surgery and identify surgical subtypes associated with cardiovascular events using a large administrative database of United States hospital admissions. Design, Setting, Participants Patients who underwent major non-cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
217
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 336 publications
(240 citation statements)
references
References 25 publications
7
217
0
16
Order By: Relevance
“…[6] Patients were included if they had a principal International Classification of Diseases, Ninth Revision (ICD-9) procedure code for a major therapeutic operating room procedure (HCUP Procedure Class 4). Principal CCS procedure codes, which represent an aggregate of relevant primary ICD-9 procedure codes by surgical subtype, were used to exclude patients who underwent cardiac procedures (n=1,655,567), cardiac surgery and cardiac transplantation (n=582,726), bone marrow transplantation (n=18,151), ophthalmologic surgery (n=13,342), radiation therapy (n=9,817), dental surgery (n=1,779), and non-operating room procedures (n=386) as a principal in-hospital procedure.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Patients were included if they had a principal International Classification of Diseases, Ninth Revision (ICD-9) procedure code for a major therapeutic operating room procedure (HCUP Procedure Class 4). Principal CCS procedure codes, which represent an aggregate of relevant primary ICD-9 procedure codes by surgical subtype, were used to exclude patients who underwent cardiac procedures (n=1,655,567), cardiac surgery and cardiac transplantation (n=582,726), bone marrow transplantation (n=18,151), ophthalmologic surgery (n=13,342), radiation therapy (n=9,817), dental surgery (n=1,779), and non-operating room procedures (n=386) as a principal in-hospital procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Patients at elevated risk for cardiovascular complications are prone to perioperative adverse cardiac events, such as myocardial injury after non-cardiac surgery (MINS) (1) and face higher perioperative mortality (1)(2)(3)(4). Atherosclerosis and its complications are driven by systemic inflammation (5), however the mechanisms underlying perioperative cardiovascular complications are not fully understood (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the world, there are more than 300 million major surgery each year, and major cardiovascular adverse events are a significant cause of perioperative morbidity and mortality. 1 This certainly relates to the nature of anesthetic agents that are mostly cardiovascular-depressant. Anesthetic agents such as propofol, ketamine, opioids, inhalation anesthetic agents, and many others, can directly affect the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…This frequently reduces the alertness of an anesthesiologist, especially when performing perioperative monitoring. A study from Smilowitz et al, 1 showed that out of 10,581,621 patients admitted to hospital for major non-cardiac surgery plans, 317,479 (3%) patients had experienced major cardiac events. Which can be illustrated that major cardiac events occur in 1 in 33 patients treated for major non-cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%